Association between dietary sugar intake and colorectal adenoma among cancer screening examinees in Japan. Issue 10 (26th August 2020) - Cho, Hourin; Budhathoki, Sanjeev; Kanehara, Rieko; Goto, Atsushi; Yamaji, Taiki; Kakugawa, Yasuo; Saito, Yutaka; Matsuda, Takahisa; Iwasaki, Motoki; Tsugane, Shoichiro
Abstract: Although intake of highly sugary foods is considered to be a potential risk factor for colorectal cancer through hyperinsulinemia, the association of sugar intake and colorectal adenoma, a precursor lesion to most colorectal cancer, is poorly understood, particularly in Asian populations. We undertook a cross‐sectional study in a Japanese population to investigate the association between dietary sugar intake and the prevalence of colorectal adenoma. Study subjects were selected from participants who underwent magnifying colonoscopy with dye spraying as part of a cancer screening program and who responded to a self‐administered questionnaire before the colonoscopy. A total of 738 cases with colorectal adenoma and 697 controls were enrolled. Dietary intakes of glucose, fructose, galactose, sucrose, maltose, lactose, and total sugars (sum of these six mono‐ or disaccharides) were calculated from a food frequency questionnaire, and divided into quartiles based on the distribution among controls. Odds ratios and 95% confidence intervals of colorectal adenoma were estimated using unconditional logistic regression models, with adjustment for potential confounding factors. Total sugar intake was not significantly associated with the prevalence of colorectal adenoma (odds ratio for the highest intake group compared to reference group = 1.18; 95% confidence interval, 0.81‐1.73; P for trend = .34). Furthermore, no statistically significant positive associations were observed for any of the six mono‐ or disaccharides. Findings were similar on additional analyses by site, size, and number of adenomas. Our findings do not support an association between high sugar intake and increased odds ratios of colorectal adenoma. Abstract : In this case‐control study in a Japanese population, dietary intakes of sugars were calculated from a food frequency questionnaire and odds ratios and 95% confidence intervals of colorectal adenoma according to sugar intake were estimated using logistic regression models. We found that sugar intake was not significantly associated with the prevalence of colorectal adenoma. Furthermore, no statistically significant positive associations were observed for any of the six mono‐ or disaccharides.